Islamic Business Ethics and MSME Performance: A Bibliometric Analysis and Future Research Agenda - Kamil Ibrahim; Thierno Abdoulaye Balde; Manda Nevy Antika; Masiyah Kholmi (Al-Ubudiyah: Jurnal Pendidikan dan Studi Islam, 2026)
This study aims to systematically map the development of research on Islamic Business Ethics (IBE) and MSME performance through a bibliometric analysis approach. The increasing importance of ethical business practices and the strategic role of Micro, Small, and Medium Enterprises (MSMEs) in economic development have generated growing academic interest in understanding how Islamic ethical values contribute to organizational performance and sustainability. Data were collected from the Scopus database covering publications from 2016 to 2026 and analyzed using VOSviewer. The analysis included publication trends, keyword co-occurrence, citation analysis, and thematic mapping to identify the intellectual structure and emerging research directions within the field. The findings indicate a generally increasing trend in publications, particularly after 2020, reflecting the growing relevance of Islamic Business Ethics in contemporary business studies. Keyword co-occurrence analysis revealed three major dimensions of research: normative, practical, and institutional–behavioral dimensions. While the literature is predominantly focused on Islamic values, ethics, and finance-related topics, studies explicitly linking Islamic Business Ethics to MSME performance remain limited. Recent research demonstrates a shift toward sustainability, innovation, entrepreneurship, and performance-oriented themes. The study identifies significant research gaps and proposes future research agendas focusing on the direct and indirect effects of Islamic Business Ethics on MSME performance, sustainability, and competitive advantage. These findings contribute to a deeper understanding of the evolving research landscape and provide directions for future empirical investigations.